Veterinary migration: why do vets move abroad?. (18th March 2017) - Enticott, G.
Abstract : Migration of veterinary professionals to and from the UK has important consequences for the profession. Gareth Enticott believes that not enough is known about the motivations for migration and that more time should be spent analysing the reasons.